Kajian Kriteria Perencanaan Dan Metode Pelaksanaan Struktur Reservoir - TARIGAN, Johannes; Tarigan, Simon Dertha; Sitanggang, Ernie Shinta Yosephine; Ginting, Philip Amsal Aprianto (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
Reservoir is a building used as a place to hold clean water before being distributed. Artificial resevoir can be a steel tank or reinforced concrete tub. For reservoir that is planned to accommodate large amounts of water capacity, it is usually more effective to use reinforced concrete. Evaluation and analysis of reservoir construction is one of the important aspects to ensure that the reservoir design meets the requirements of strength and stability, as well as functional abilities. The problem that often occurs in reservoir buildings is the occurrence of uncontrolled uplift which results upward movement in the construction of the reservoir, and also the reservoir building often decreases differently due to improper foundation systems. This different decline resulted in cracks on the floor of the reservoir building which in turn will cause damage and malfunction of the reservoir construction. This paper contains a study of planning evaluation and analysis, and the method of implementation of severalconstructions of reservoir structures that have been carried out. The results of this study are expected to provide input and help planners and contractors to build reinforced concrete reservoirs that comply with the correct planning criteria, so that the building can function properly as planned.